1999
DOI: 10.1001/jama.281.20.1911
|View full text |Cite
|
Sign up to set email alerts
|

Tourism and Hotel Revenues Before and After Passage of Smoke-Free Restaurant Ordinances

Abstract: Smoke-free ordinances do not appear to adversely affect, and may increase, tourist business.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(38 citation statements)
references
References 17 publications
1
37
0
Order By: Relevance
“…COTTI, 2007;ALPERT et al, 2007;THOMPSON et al, 2008). Less common indicators include purchasing prices of restaurants (ALAMAR & GLANTZ, 2004) tourism demand (GLANTZ & CHARLESWORTH, 1999) or non-economic indicators like air quality (ALPERT et al, 2007). SCOLLO & LAL (2008) provide an extensive survey on these strands of research.…”
Section: Literature Surveymentioning
confidence: 99%
“…COTTI, 2007;ALPERT et al, 2007;THOMPSON et al, 2008). Less common indicators include purchasing prices of restaurants (ALAMAR & GLANTZ, 2004) tourism demand (GLANTZ & CHARLESWORTH, 1999) or non-economic indicators like air quality (ALPERT et al, 2007). SCOLLO & LAL (2008) provide an extensive survey on these strands of research.…”
Section: Literature Surveymentioning
confidence: 99%
“…23 Analysis of pre and postsmoking ban business revenue has consistently revealed no negative impact on profits made by restaurants, bars, hotels, and general tourism establishments. [24][25][26][27] Increasing tobacco taxes will negatively impact tobacco sales, especially to adolescents, and produce more money for tobacco prevention. 28 Ending the Tobacco Problem: A Blueprint for the Nation is a road map for America to irreversibly commit to ending the tobacco epidemic and can serve as a wealth of information for physicians hoping to fight tobacco on a community or national level.…”
Section: Population Barriers To Smoking Cessationmentioning
confidence: 99%
“…Kjell Bjartveit (1998;Bjartveit & WHO, 2003) has shown that Norway's 1975 ban on tobacco advertising did not adversely affect newspaper and ad agency revenues, despite dire pre-ban predictions from both groups. Similarly, there are many recent studies documenting the minimal or even beneficial effects of smoke-free laws on bar, restaurant, and hotel revenues (Bartosch & Pope, 2002;Cremieux & Ouellette, 2001;Glantz & Charlesworth, 1999;Huang, De, & McCusker, 2004;Hyland, Cummings, & Nauenberg, 1999;Hyland, Puli, Cummings, & Sciandra, 2003;Scollo, Lal, Hyland, & Glantz, 2003). The 2003 advertising ban thus affords a unique opportunity to determine how key beneficiaries of tobacco industry largesse-campus newspapers-fared when deprived of this revenue stream.…”
Section: Quantitative Findingsmentioning
confidence: 99%